2007
DOI: 10.1073/pnas.0609644104
|View full text |Cite
|
Sign up to set email alerts
|

Monoalkyl sulfates as alkylating agents in water, alkylsulfatase rate enhancements, and the “energy-rich” nature of sulfate half-esters

Abstract: Alkyl sulfate monoesters are involved in cell signaling and structure. Alkyl sulfates are also present in many commercial detergents. Here, we show that monomethyl sulfate acts as an efficient alkylating agent in water, reacting spontaneously with oxygen nucleophiles >100-fold more rapidly than do alkylsulfonium ions, the usual methyl donors in living organisms. These reactions of methyl sulfate, which are much more rapid than its hydrolysis, are insensitive to the nature of the attacking nucleophile, with a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…This reaction was described by Wolfenden et al 60 and was found to have a very low rate at a pH around neutral, but which accelerates in acidic or alkaline environment and with temperature. Although there exist indications for a slight acidity of the lubricant (and therefore a preference of equation (5)), the synchronous occurrence of the reactions following equations (4) and (5) and the dissociation of HSO À 4 result in…”
Section: Beneficial Tribofilm From Sulfate Anionmentioning
confidence: 84%
“…This reaction was described by Wolfenden et al 60 and was found to have a very low rate at a pH around neutral, but which accelerates in acidic or alkaline environment and with temperature. Although there exist indications for a slight acidity of the lubricant (and therefore a preference of equation (5)), the synchronous occurrence of the reactions following equations (4) and (5) and the dissociation of HSO À 4 result in…”
Section: Beneficial Tribofilm From Sulfate Anionmentioning
confidence: 84%
“…Activation energies of corresponding reactions are calculated directly and used as theoretical determinants for the possibility of corresponding exchange channels. Hydrolysis of sulfate and phosphate esters also play a central role in a variety of biochemical processes and modeling such systems is feasible (Rodiguez-Lopez et al, 2001;Akola and Jones, 2003;Wolfenden and Yuan, 2007, and references cited therein). Independently, we examine our model results on the potential for APS-sulfate-water oxygen exchange using in vitro experiments that utilize triple-oxygen-isotope labeled solutions.…”
Section: Introductionmentioning
confidence: 99%
“…As the equilibrium constant K is the actual experimental property measured, a linear regression analysis of lnK vs. 1/T was performed to yield the thermodynamic parameters H hyd and −T S hyd . The monofunctional primary organosulfate hydrolysis thermodynamics parameters were previously reported for the methyl (Wolfenden and Yuan, 2007), the ethyl (Clark and Williams, 1957) and the 1-butyl (Minerath et al, 2008) systems (which were measured at varying sulfuric acid and water activities) were reanalyzed in terms of this standard definition of the equilibrium constant, and the thermodynamic parameters for these systems are reported in Table 1. The thermodynamic parameters obtained for the difunctional primary or secondary butyl organosulfate systems in the present work are reported in Table 2.…”
Section: Experimental Determination Of Thermodynamics Parameters For mentioning
confidence: 99%